علاقة واثر اللقاء الخدمي في سلوك مواطنة الزبون - دراسة استطلاعية لآراء عينة من مقدمي الخدمة والزبائن في القطاع الفندقي لمحافظة النجف الاشرف - يوسف حجيم الطائي; حاكم جبوري الخفاجي (مجلة الغري للعلوم الاقتصادية والادارية)
المستخلص هدفت الد ا رسة الى تشخيص العلاقة بين اللقاء الخدمي وسلوك مواطنة الزبون من خلال عينتين في القطاع الفندقي لمحافظة النجف الاشرف، العينة الاولى لمقدمي الخدمة بلغت( 184 ) والعينة الثانية لزبائن لإيجاد (SPSS, Var. الفندق بلغت ( 212 ) وبعد اج ا رء التحليل الاحصائي باعتماد البرنامج الاحصائي ( 21 الحلول الملائمة لمشكلة الد ا رسة المتمثلة بتحديد وتشخيص اثر اللقاء الخدمي اثناء تقديم الخدمة للزبون ومدى انعكاسه على سلوك مواطنة الزبون ودوره التطوعي تجاه المنظمات عينة الد ا رسة بهدف تحسين الخدمة الفندقية المقدمة للزبون، وتحسين اداء مقدم الخدمة والقطاع الفندقي لمحافظة النجف والع ا رق. توصلت الد ا رسة الى مجموعة من الاستنتاجات وأهمها ان مقدمي الخدمة لهم دور كبير في تقوية العلاقة بينهم وبين الزبون من خلال التكيف مع حاجاته وطلباته والقضاء على حالات الارباك او تقليلها والتي تحصل نتيجة الخدمات الطارئة او الموقفية بالاعتماد على خب ا رته وقد ا رته مما يحفز سلوك المواطنة لدى الزبون ليقدم توصياته ومقترحاته ومساعدته للزبائن ومعلوماته وتقييمه للخدمة المقدمة، في الفنادق عينة الد ا رسة. اما اهم التوصيات التي جاءت بها الد ا رسة من اجل تعزيز متطلبات نجاح اللقاء الخدمي بين مقدم الخدمة والزبون من خلال اليات منها اختيار مقدمي خدمة يمتلكون المؤهل العلمي والمهارة وادخالهم بب ا رمج تدريبية بهدف الحد من حالات الفشل التي ت ا رفق الخدمة، وانعاشها والتكيف مع حاجات الزبون، فضلا عن تحديد معايير تقديم الخدمة حتى تكون التصرفات العفوية لمقدم الخدمة محدودة، مما سيسهم في تبنيه لسلوك مواطنة الزبون تجاه الفنادق عينة الد ا رسة Abstract: This study aims to diagnose the relationship and effect between service encounters and citizenship customer behavior. Mean whith by analysis the opinions of two samples in the hotel sector of the province of Najaf. The first sample of service providers was amounted (184) and the second sample to customers was amounted (212). After statistical analysis of data by using (SPSS, Var. 21) program, which used to find appropriate solutions of the study problem identification. Likewise, diagnosis of the impact of service encounters, while providing the service to the customer and the extent of its reflection on the behavior of citizenship customer. Moreover, analysis its volunteerism role towards the study sample, in order to improve hotel service provided to the customer then to improve the performance of the service provider and hotel sector at the province of Najaf in the Iraq. The results found a set of conclusions the most important, as it turns out that the service providers have a major role in strengthening the relationship, including customer and between through adapt to the needs and requests, and the elimination of confusion or reduced and that you get as a result of the emergency services or attitudinal relying on his experience and abilities which stimulates citizenship behavior of the customer to make recommendations and suggestions and assistance to customers and information and assessment of the service provided According to, the specific service times without this delay its demonstrates the ability and 104 expertise possessed by his work in making the customer rushes to help the organization to achieve a good reputation from side to side, the information derived from it to improve and develop the service provided potential customers a voluntary role in the hotels of the study sample the most important recommendations that came out the study in order to promote the success of the service encounters between the service and the customer provider requirements through mechanisms including the selection of service providers have the qualification, skill and admitted training programs. In order to, reduce the incidence of failure that accompanies the service, and rehabilitation and adapt to customer needs, as well as identifying standards of service. Outstanding the spontaneous acts of limited service provider, which will contribute to the adoption of the behavior of the customer toward citizenship research sample hotels